Combined angiotensin-converting enzyme and aminopeptidase inhibition for treatment of experimental ventilator-induced lung injury in mice - Mao, Xinjun; Tretter, Verena; Zhu, Yi; Kraft, Felix; Vigl, Benjamin; Poglitsch, Marko; Ullrich, Roman; Abraham, Dietmar; Krenn, Katharina (Frontiers in Physiology, 2023)
Ventilator-induced lung injury (VILI) may aggravate critical illness. Although angiotensin-converting enzyme (ACE) inhibition has beneficial effects in VILI, its clinical application is impeded by concomitant hypotension. We hypothesized that the aminopeptidase inhibitor ALT-00 may oppose the hypotension induced by an ACE inhibitor, and that this combination would activate the alternative renin-angiotensin system (RAS) axis to counteract VILI. Methods: In separate experiments, C57BL/6 mice were mechanically ventilated with low (LVT, 6 mL/kg) and high tidal volumes (HVT, 30 mL/kg) for 4 hours or remained unventilated (sham). HVT-ventilated mice were treated with lisinopril (0.15 µg/kg/min) +/- ALT-00 at 2.7, 10 or 100 µg/kg/min. Blood pressure was recorded at baseline and after 4 hours. Lung histology was evaluated for VILI and the angiotensin (Ang) metabolite profile in plasma (equilibrium levels of Ang I, Ang II, Ang III, Ang IV, Ang 1-7 and Ang 1-5) was measured with liquid chromatography tandem mass spectrometry at the end of the experiment. Angiotensin concentration-based markers for renin, ACE and alternative RAS activities were calculated. Results: HVT-ventilated mice treated with lisinopril showed a significant drop in the mean arterial pressure at 4 hours compared to baseline, which was prevented by adding ALT-00 at 10 and 100 µg/kg/min. Ang I, Ang II and Ang 1-7 plasma equilibrium levels were elevated in the HVT group versus the sham group. Lisinopril reduced Ang II and slightly increased Ang I and Ang 1-7 levels versus the untreated HVT group. Adding ALT-00 at 10 and 100 µg/kg/min increased Ang I and Ang 1-7 levels versus the HVT group, and partly prevented the downregulation of Ang II levels caused by lisinopril. The histological lung injury score was higher in the HVT group versus the sham and LVT groups, and was attenuated by lisinopril +/- ALT-00 at all dose levels. Conclusions: Combined ACE plus aminopeptidase inhibition prevented systemic hypotension and maintained the protective effect of lisinopril. In this study, a combination of lisinopril and ALT-00 at 10 µg/kg/min appeared to be the optimal approach, which may represent a promising strategy to counteract VILI that merits further exploration.